Impact of systemic risk regulation on optimal policies and asset prices - Bernard, Carole; Cui, Xuecan (Journal of Banking & Finance, 2023)
Although a few systemic risk management approaches have been proposed in the literature and implemented in industry, such as stress test-based scenarios, the impact of such regulations remains unclear. In this paper, we present a theoretical framework to study the impact of systemic risk management on financial institutions’ optimal wealth policies and asset prices in equilibrium. Specifically, we study the impact of the conditional VaR (CoVaR) and systemic expected shortfall (SES) constraints and illustrate the potential adverse effects of conditional risk measures when the market is under stress. We find that a proper choice of the SES constraint, especially based on option-implied information, may effectively reduce these impacts.